(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this paper reviews an Iberian inscription published forty years ago and collected some unpublished recovered in Segrià region, located in the lower reaches of the river Segre, in the west of Catalonia, an area that corresponds to the center of historical Ilergetes. It confirms the dual system knowledge during the fourth century BC and the widespread practice of Iberian epigraphic in Late Iberian Period. Also gives news of the first inscriptions from Ilerda.